2016
DOI: 10.1001/jamaoto.2016.0335
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TargetableERBB2Aberrations in Head and Neck Squamous Cell Carcinoma

Abstract: Importance HER2 is an important drug target in breast cancer, where anti-HER2 therapy has been shown to lead to improvements in disease recurrence and overall survival. HER2 status in head and neck squamous cell carcinoma (HNSCC) has not been well studied. Identification of HER2 positive tumors and characterization of response to HER2 therapy could lead to targeted treatment options in HNSCC. Objective To identify HER2 aberrations in HNSCCs and investigate potential for HER2 targeted therapy in HNSCCs. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 40 publications
7
34
1
Order By: Relevance
“…In a recent study only 2/42 (5%) laryngeal SCCs and 2/94 (2%) oral cavity SCCs were positive for ErbB2 (HER2) overexpression on immunohistochemistry. (206) Earlier studies have reported an inverse relationship between EGFR and HER2 expression although this was not observed by Maubec et al (2005) in metastatic cSCC and the absence of HER 2 positivity in our cohort precluded this assessment. (189) The lack of HER2 expression in these tumours mechanistically is likely to lead to higher EGFR activation as EGFR will homodimerize in the absence of its preferred heterodimeric partner.…”
Section: Her2 Does Not Play a Significant Role In Perineural Spread Ocontrasting
confidence: 55%
“…In a recent study only 2/42 (5%) laryngeal SCCs and 2/94 (2%) oral cavity SCCs were positive for ErbB2 (HER2) overexpression on immunohistochemistry. (206) Earlier studies have reported an inverse relationship between EGFR and HER2 expression although this was not observed by Maubec et al (2005) in metastatic cSCC and the absence of HER 2 positivity in our cohort precluded this assessment. (189) The lack of HER2 expression in these tumours mechanistically is likely to lead to higher EGFR activation as EGFR will homodimerize in the absence of its preferred heterodimeric partner.…”
Section: Her2 Does Not Play a Significant Role In Perineural Spread Ocontrasting
confidence: 55%
“…Around 3% of SCCHN patient tumours express HER2, whereas activation of Src has been commonly involved in epithelial–mesenchymal transition or erlotinib resistance of SCCHN. 3133 Moreover, one-fifth of breast cancer patient tumours have excessive HER2 expression, which means 80% of breast cancers do not possess dysregulated HER2. This suggests that in HER2 negative breast cancer and most cases of head and neck cancer, LDHA is not tyrosine phosphorylated by oncogenic receptor tyrosine kinases but that tyrosine phosphorylation of LDHA by kinase cascades involving cytoplasmic tyrosine kinases such as Src may mediate LDHA activation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there have been reports of remarkable response of agents used in precision medicine paradigms that have not been traditionally used in a specific cancer type [77]. Early investigations into genetic aberrations in HNSCC suggest that multiple agents FDA-approved in other cancers may have potential in HNSCCs, such as using trastuzumab (currently approved for breast and gastrointestinal cancer) in ERBB2 positive HNSCCS [78]. …”
Section: Translating Studies Into Treatmentmentioning
confidence: 99%